Ultrassonografia testicular em bovinos jovens da raça Nelore criados em sistema extensivo - Cardilli, D.J. [UNESP]; Toniollo, Gilson Hélio [UNESP]; Pastore, A.A.; Canola, J.C.; Oliveira, J.A.; Mercadante, M.E.Z. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2012)
Este estudo visou avaliar o padrão ultrassonográfico do parênquima testicular de touros jovens da raça Nelore, desde a fase peripuberal até a puberdade, estabelecer padrões fisiológicos e também verificar se existe diferença de ecogenicidade entre animais púberes e pré-púberes na mesma idade. Foram realizados exames ecográficos dos testículos de 19 bovinos aos 10, 12, 14, 16 e 18 meses de idade. O padrão ultrassonográfico do parênquima testicular mostrou-se homogêneo e com ecogenicidade moderada. A ecogenicidade testicular aumentou em proporção direta com a idade dos animais. Não houve diferença significativa entre a ecogenicidade testicular de animais púberes e pré-púberes na mesma idade.

The aim of this study was to evaluate the testicular parenchyma of young Nelore bulls through standard ultrasound, in order to establish the physiological standards, as well as differences in echogenicity between pre-pubescent and pubescent animals of the same age. Testis of 19 young Nelore bulls were evaluated by ultrasonography at 10, 12, 14, 16 and 18 months old. Homogeneous and moderate testicular parenchyma echogenicity was observed in all animals. Testicular echogenicity increased with the age of the animal. There were no significant differences in testicular echogenicity between pre-pubescent and pubescent animals with the same age.
Testicular ultrasonography in young Nelore bulls raised in extensive management system
Keywords: male reproductive tract; echography; Bovine; trato reprodutor masculino; Ecografia; Bovino